Decade Trends of Augmented Reality: Challenges And Opportunities In Elementary Science Learning 2017–2026 - Prelia Dwi Amanah; Sura Juddin; Gesti Maharani; Gunawan Gunawan (Indonesian Publication Center, 2026)
This study aims to map the research trends of Augmented Reality in elementary science learning from 2017 to 2026 by examining research focus, implementation challenges, and future development opportunities. A systematic review employing bibliometric analysis was conducted on scientific publications indexed in Google Scholar and Dimensions.ai. Data were extracted using Publish or Perish and analyzed with VOSviewer to visualize publication patterns, keyword networks, and thematic evolution. The findings indicate a significant increase in AR-related publications in elementary science education, particularly after the COVID-19 pandemic, accompanied by a shift from technological exploration to pedagogical integration and learning outcomes. Based on the ANZSRC 2020 classification, the research is predominantly situated within Information and Computing Sciences and Education. Furthermore, SDGs analysis reveals a strong contribution to SDG 4 (Quality Education). Key challenges include limited technological infrastructure, insufficient teacher digital literacy, and a lack of context-responsive instructional design. Nevertheless, AR demonstrates substantial potential to support interactive, learner-centered, and sustainable elementary science learning. These findings highlight AR as a strategic educational technology capable of enhancing meaningful science learning when integrated with sound pedagogical frameworks.